Serapan Hara N, P, K dan Pertumbuhan Tanaman Padi (Oryza sativa L.) di Medium Gambut yang Diaplikasikan Amelioran Dregs dan Pupuk N, P, K (Jurnal Agro Teknologi Tropika, 2012)
Peat soil is one of the ecosystems which considerable potential in Riau Province to be developed as agricultural land.Besides low nutrient availability, other factors that inhibit the growth of plants on peat soil are higher organic acid content.To overcome this, dregs can be applied. The research has been conducted the experimental farm of Agriculture Faculty,University of Riau, Pekanbaru on April-Augst 2011. The experimental units were arranged in factorial completely rendomizeddesign. The first factor is the dose of dregs consisting of three levels: D0 = without giving dregs, D1 = 2.5 tons/ha of dreg,and D2 = 5 tons/ha of dreg. The second factor is the dose of N, P, and K fertilizers consisting of three levels: P1 =recommended dosage, P2 = 1.5 x the recommended dosage, and P3 = 2 x recommended dosage. The results showed that thedoses of dregs at 2.5 tons/ha and 5 tons/ha in general tended to increase the height, the maximum number of tillers, dryweight of roots, and plant canopy dry weight at age 48 HST, comparing to no dregs at each dose of N, P, and K fertilizers(1, 1.5 and 2 times the recommended dosage). Nutrient of N absorption by roots and canopy, respectively increased by29.87% and 299.08%, nutrient of P absorption by roots and canopy increased by 13.89% and 239.52, and nutrient of Kabsorption by roots and canopy increased by 16.97% and 153% with the application of 5 tons/ha dregs followed by theapplication of N, P, K fertilizer with 2 times of the recommended dosage compared to the application of N, P, K fertilizer with1 times of the recommended dosage that followed no dregs application.Keywords: peat soil, paddy, ameliorant dregs, NPK nutrient